2011
DOI: 10.3389/fpsyg.2011.00055
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sensory Facilitation Reveals Neural Interactions between Visual and Tactile Motion in Humans

Abstract: Many recent studies show that the human brain integrates information across the different senses and that stimuli of one sensory modality can enhance the perception of other modalities. Here we study the processes that mediate cross-modal facilitation and summation between visual and tactile motion. We find that while summation produced a generic, non-specific improvement of thresholds, probably reflecting higher-order interaction of decision signals, facilitation reveals a strong, direction-specific interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 55 publications
7
34
0
Order By: Relevance
“…Arabzadeh et al [49] demonstrated that a visual flash presented near the fingers during a simple haptic discrimination task was able to reproduce the classical ‘dipper effect’ and improve near-threshold stimulus discriminability, as if the haptic signal had a direct input into the visual mechanism and provided the equivalent of a contrast pedestal. Similarly, in a speed discrimination task, Gori et al [50] showed cross-sensory facilitation between vision and touch that resulted in a two-fold improvement of discrimination thresholds that was specific for matched visuo-haptic motion direction. Together, these two findings suggest that the haptic signal in our experiment, which is likely to be broadly tuned after being remapped into visual coordinates and fed back to early visual cortex, effectively provided a contrast pedestal for vision, thereby improving visual orientation discrimination and producing a very sharp tuning.…”
Section: Discussionmentioning
confidence: 94%
“…Arabzadeh et al [49] demonstrated that a visual flash presented near the fingers during a simple haptic discrimination task was able to reproduce the classical ‘dipper effect’ and improve near-threshold stimulus discriminability, as if the haptic signal had a direct input into the visual mechanism and provided the equivalent of a contrast pedestal. Similarly, in a speed discrimination task, Gori et al [50] showed cross-sensory facilitation between vision and touch that resulted in a two-fold improvement of discrimination thresholds that was specific for matched visuo-haptic motion direction. Together, these two findings suggest that the haptic signal in our experiment, which is likely to be broadly tuned after being remapped into visual coordinates and fed back to early visual cortex, effectively provided a contrast pedestal for vision, thereby improving visual orientation discrimination and producing a very sharp tuning.…”
Section: Discussionmentioning
confidence: 94%
“…Humans are sensitive to tactile motion cues, which do not require temporal integration, such as the orientation, the direction, and the speed of motion [1][2][3]. To form a global motion percept, the tactile system spatially integrates the local motion signals provided by primary afferents across the skin [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence for cross-modal synergism when stimulation from one modality is combined with that from another. After the seminal work by McGurk and MacDonald, 1976) that showed a cross-modal interaction between auditory and visual processing, cross-modal modulation and synergism have been reported across a number of sensory combinations such as between vision and audition (McDonald and Ward, 2000; Watanabe and Shimojo, 2001; Kayser et al, 2009), vision and olfaction (Zellner and Kautz, 1990; Zellner and Whitten, 1999; Koza et al, 2005; Dematte et al, 2009), vision and touch (Kennett et al, 2001; Ro et al, 2004; Gori et al, 2011), olfaction and audition (La Buisonniere-Ariza et al, 2012), somatosensation and audition, as well as audition and gustation (North, 2012). …”
Section: Discussionmentioning
confidence: 99%